The handbook of market intelligence : understand, compete and grow in global markets - Hedin, Hans.; Hirvensalo, Irmeli; Vaarnas, Markko (Chichester, West Sussex : Wiley, 2014)
"This book provides a very useful and practical framework to guide the development of a Market Intelligence function that serves as a tool for competitive advantage. The use of multiple and diverse business cases helps readers to understand the implementation of key concepts and provides a set of practical lessons to facilitate this important journey for any organization."--Carlos Jose Fonseca, SVP/Group Head Global Marketing Strategy, Planning and Analytics, MasterCard "Forward looking market understanding is what any CEO needs for securing successful business today and into the future. But.
Preface to the second edition -- About the authors -- About global intelligence alliance -- Market intelligence in global organizations -- Market intelligence : drivers and benefits -- Market intelligence in global organizations : survey findings in 2013 -- Roadmap to world class market intelligence -- Key success factors of world class market intelligence -- Intelligence scope : determining the purpose, target groups and focus areas of an intelligence program -- Intelligence process : turning random data into meaningful insight -- Intelligence deliverables : building a high-impact market intelligence product portfolio -- Intelligence tools : collecting, storing and disseminating intelligence -- Intelligence organization : the people and resources that generate the impact -- Intelligence culture : engaging the organization in market intelligence -- Market intelligence for key user groups -- Market intelligence for current awareness across the organization -- Market intelligence for strategic planning -- Market intelligence for marketing, sales and account management -- Market intelligence for innovation and product life cycle management -- Market intelligence for supply chain management -- Developing world class market intelligence programs -- Implementing market intelligence programs -- How to develop an existing market intelligence program for greater impact -- Measuring the impact of mi -- Trends in market intelligence -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business intelligence; Marketing research; Business intelligence -- Case studies; Marketing research -- Case studies; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business intelligence; Marketing research; Electronic books; Case studies